The materiality of trust: Beauty consumption of young Chinese women through e-commerce live-streaming - Xiao, Fan (AoIR Selected Papers of Internet Research, 2026)
Growing up with China’s rapid economic expansion and globalization, young Chinese women (aged under 35) living in urban cities found them facing an increasingly consumerist environment, with advanced media-commerce system that promotes certain ideas of womanhood and beauty ideals to incite beauty consumption. This study critically examines how young urban Chinese women negotiate consumerist beauty knowledge with needs of self-care and class-specific consumption. In this process, digital media plays a central in the circulation of beauty care information and gradually converge with retailing platforms. With multimodal analysis and in-depth interview, this study focuses on the followers of Li Jiaqi, China’s most influential beauty e-commerce streamer, to explores the gendered, consumerist Chinese beauty culture, which deeply integrates with media-commerce platforms. Findings from this study suggest that the social construction of "beauty care" is an important device for young women to imagine and practice maturity, personal safety, and class status, displaying a dialectic relationship between body anxiety and feminist awareness.